The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/nu10111778
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Controlled Study to Evaluate the Effects of Yogurt Enriched with Lactococcus lactis 11/19-B1 and Bifidobacterium lactis on Serum Low-Density Lipoprotein Level and Antigen-Specific Interferon-γ Releasing Ability

Abstract: In order to clarify the effects of the Lactococcus lactis (L. lactis) 11/19-B1 strain, a double-blind controlled study of yogurt fermented with the strain was carried out. For the study, two kinds of yogurt, the control and test yogurt, were prepared; the control yogurt was fermented with Streptococcus thermophiles, Lactobacillus delbrueckii subspecies bulgaricus, and Lactobacillus acidophilus, and the test yogurt was enriched with L. lactis 11/19-B1 and Bifidobacterium lactis (B. lactis) BB-12 strains. Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…The mean probiotic administration was 67.01 ± 38.72 days (range = 28–186 days). Probiotic, not synbiotic, interventions were predominantly conducted ( n = 54) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 88 , 89 ]. Probiotic powders were administered in 15 studies [ 31 , 36 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean probiotic administration was 67.01 ± 38.72 days (range = 28–186 days). Probiotic, not synbiotic, interventions were predominantly conducted ( n = 54) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 88 , 89 ]. Probiotic powders were administered in 15 studies [ 31 , 36 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The daily doses varied between 10 6 and 10 10 CFU (colony-forming units). The trials were financed by only industry budgets in 20 ( n = 20) [ 29 , 30 , 33 , 34 , 39 , 41 , 42 , 46 , 47 , 48 , 55 , 64 , 67 , 69 , 75 , 76 , 78 , 79 , 83 , 84 ]. Studies were financed only by academic resources in 10 studies ( n = 10) [ 31 , 32 , 35 , 37 , 40 , 43 , 44 , 52 , 58 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This genus does not gain too much interest for its probiotic activity because the main attention is focused on the other LAB genera as Lactobacillus and Bifidobacterium [ 63 ]. However, some studies have shown the beneficial effects of products fermented with Lactococcus in the gut [ 64 ]. A previous study on subjects with slightly elevated blood lipid or blood sugar levels demonstrated that the administration of yogurt fermented with the Lactococcus lactis 11/19-B1 strain for 8 weeks significantly reduced total cholesterol, LDL and LDL/HDL ratio [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown the beneficial effects of products fermented with Lactococcus in the gut [ 64 ]. A previous study on subjects with slightly elevated blood lipid or blood sugar levels demonstrated that the administration of yogurt fermented with the Lactococcus lactis 11/19-B1 strain for 8 weeks significantly reduced total cholesterol, LDL and LDL/HDL ratio [ 64 ]. Moreover, 8 weeks of drinking skim milk fermented with Lactococcus genera has shown a positive impact on the systolic blood pressure level in prehypertensive individuals [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the L. lactis 11/19-B1 strain, isolated from the surface of kiwifruit, markedly stimulates innate immunity in silkworms and shows some differences in sugar utilization and enzymatic characteristics in comparison with other L. lactis strains ( 1 ). Furthermore, we reported that the intake of yogurt containing 11/19-B1 significantly decreased the level of low-density lipoproteins (LDLs) in high-LDL volunteers in comparison to that of the control yogurt ( 2 ). Moreover, 11/19-B1 improved atopic dermatitis (AD) in humans and AD-related dorsal skin and ear lesions in a 1-fluoro-2,4-dinitrobenzene-induced AD mouse model ( 3 ).…”
Section: Announcementmentioning
confidence: 99%